The challenge of cytotoxic T cell responses in carcinoma with a focus on lung carcinoma - Dash, Aditya; Banisadr, Afsheen; Al Dikka, Donivian; Johns, Scott C.; Fuster, Mark M. (Frontiers in Oncology, 2025)
Immunity during cancer progression involves critical responses that may be harnessed to augment anti-tumor cytotoxicity. A potent arm of immunity in cancer involves cytotoxic T cells (a key CD8+ T-lymphocyte subset): Anti-tumor responses by such cells optimally involve sensitization and acquired responses to tumor antigens by antigen presenting cells. Many tumor microenvironment (TME) biophysical and functional limitations in carcinomas limit robust achievement of this ideal cellular-immunologic pathway. This is especially challenging in lung carcinoma, on which we focus mechanistically and with an eye to therapeutic translation. Localization of tumor-sensitized and activated CD8+ T cells to tumor “nests” with efficient tumor cytolysis involves many challenging steps. Amplifying and sustaining such responses is also a unique challenge. The variety of homeostatic and immunosuppressive obstacles often becomes overwhelming. Measuring the state of this response during lung cancer progression is also challenging, making it difficult to mount (and/or predict) T-cytotoxic responses in the heterogeneous and dynamic carcinoma antigen landscape. We investigate these challenges herein, while examining strategies to boost T-cytotoxic immunity in lung cancer through novel and emerging immunotherapeutic approaches. Beyond current immune checkpoint blockade approaches that are relatively non-specific with respect to antigen recognition by the T-cell receptor, we highlight ongoing and translational vaccines, cell-therapies, antigen-presenting cell boosting approaches, T-cell therapies, and biophysical considerations with an eye to overcome key barriers of this powerful arm of anti-tumor immunity.